Students' Creativity in Making Virtual Reality Tools from Used Items for Building Materials - Saputro, Wibowo Juli; Baiduri, Baiduri; Utomo, Dwi Priyo (Electronic Journal of Education, Social Economics and Technology, 2025)
Technology-based learning innovations and sustainability principles are now a necessity in improving the quality of education. One of the innovative approaches is the development of Virtual Reality (VR) tools from used goods as a learning medium for building spaces. This study aims to measure the level of students' creativity in making VR tools from used items and evaluate their impact on students' engagement and perception of creativity. The method used is quantitative descriptive. The sample consisted of 48 grade VIII students at SMP Darul Ihsan Muh Sragen who were selected purposively, and research instruments in the form of creativity questionnaires and work assessment rubrics based on Torrance indicators. The data was analyzed statistically descriptively to find out the average, percentage, and standard deviation of each creativity indicator. The results showed that the average score of students' creativity reached 3 out of a maximum score of 4, with aspects of flexibility and functionality prominent. In conclusion, students showed a fairly high level of creativity in utilizing used items as VR tools, although the elaboration aspect can still be improved. This research contributes to providing an alternative learning media that is cheap, environmentally friendly, and able to encourage 21st century skills such as creativity, critical thinking, and problem-solving.